Low power ultra wide-band balun LNA using noise cancellation and current-reuse techniques. (March 2017) - Vasudeva Reddy, K.; Sravani, K.; Kumar H., Prashantha
Abstract: A low power, single to differential (balun) low noise amplifier (LNA) using noise cancellation and current re-use techniques is presented for ultra wide-band applications. An upsurge balun LNA is designed using UMC 0.18-μm RF CMOS technology with an emphasis on the covenant between gain, bandwidth and power dissipation. The proposed balun exerts a differential stage on top of common gate-common source (CG-CS) stage. A CG-CS stage exploits amalgamation of CG stage (for wide-band impedance matching) and CS to curtail gain and phase imbalance, while simultaneously negating the noise and distortion of input matching transistor. The escalation of bandwidth has been accomplished using staggered tuning on CG-CS and differential stages. The stacked differential amplifier does cancellation of self noise as well as supply noise. The proposed UWB balun LNA achieves 14 dB voltage gain with agreeable input reverse isolation ( S 11 ) of < - 8 dB over the frequency range of 3.19–8.8 GHz. The minimum noise figure of 3.9 dB and P 1dB of −10.5 dBm while exhausting 3.8 mW from 1.2 V supply. The superlative performance of balun LNA is accomplished between 3.19 and 8.8 GHz with gain and phase errors below 0.2 dB and 0 . 4 0 respectively. The layout occupying 0.77 mm 2 area. The overall pre and post layout simulations of proposed LNA shows admissible agreement with theoretical predictions.